H5P-Based Matching Game for Training Graphs of Internal Forces in Structural Analysis - César De Santos-Berbel; José Ignacio Hernando García; Andrea Vázquez-Greciano (MDPI AG, 2024)
The teaching of structural analysis is essential in the training of undergraduate students who will be qualified in structural calculations. The use of games in learning can motivate students and improve their performances in evaluations. To this end, H5P-based matching games have been adopted in Moodle for a structural analysis course as an optional assignment to train graphs of internal forces (GIFs). Although the students knew that participating in the games would positively impact their grades, they were not informed of the exact number of extra points they would receive based on their performances. The engagement, motivation and performance of the students were analyzed using various statistics. Furthermore, the effectiveness of the game in facilitating knowledge acquisition was evaluated by comparing the students' performances in the games to their performances in the GIF exercises during face-to-face examinations. The study found that the students who participated in the games exhibited high levels of motivation and engagement. In addition, the results indicate that the participants had a moderately improved understanding of GIFs when taking the course examinations.